A Novel Pediatric Multisystem Inflammatory Syndrome During the COVID-19 Pandemic. Issue 10 (October 2020) - Del Greco, Giuseppina; Brady, KeriAnne; Clark, Barbara; Park, Hannah
Abstract : Abstract: In late March and early April, New York City was an epicenter of the COVID-19 pandemic. Citizens were ordered to stay at home to flatten the curve. The adult population was affected with a severe respiratory illness as well as acute kidney injury, cardiomyopathy, arrhythmia, and thromboembolism. Although children were not affected in the same manner, weeks after the peak, reports from other countries emerged about cases of pediatric patients presenting with a novel inflammatory syndrome. We present 4 patients along with their emergency department course, so providers will have a better understanding of the identification and workup of these patients. Currently, it is unclear when this inflammatory syndrome develops in respect to a COVID-19 infection. The clinical features of this syndrome seem to overlap between Kawasaki disease, toxic shock syndrome, and myocarditis. All patients presenting to our emergency department had fever, variable rash, abdominal pain, vomiting, and/or diarrhea. Patients remained persistently tachycardic and febrile despite being given proper doses of antipyretics. Severity of presentations varied among the 4 cases. All 4 patients were found to have antibodies to COVID-19. All patients required admission, but 2 required the pediatric intensive care unit for cardiac and/or respiratory support or closer monitoring. Upon follow-up on our patients, it seems that most patients are recovering with treatment, and overall, there is a low reported mortality rate.